“Cuidados de enfermería en paciente con pie diabético y complicaciones vasculares periféricas” - Yance Carriel , Fernanda Marianela (2024)
Currently, diabetes is a health problem that is constantly growing, so the nursing professional plays a very important role in control and prevention. Diabetic foot is a common and serious complication of diabetes that requires specialized care. Nursing care in patients with peripheral vascular complications is essential to prevent and treat complications such as ulcers, infections and amputations. The following case study treats a 54-year-old patient with diabetes mellitus and peripheral circulatory complications, who was admitted with hypoglycemia and ulcers in the right foot and was evidenced by a prolonged history of diabetes. Nursing played a crucial role in his care, addressing ulcer healing, glycemic control, and patient education. The care plan focused on three main diagnoses: impaired skin integrity, ineffective peripheral tissue perfusion, and risk of unstable blood glucose level. Nursing interventions included wound care, infection control, glucose monitoring, and foot care and diabetes education. The subsequent evaluation showed positive results in all areas. The wounds showed significant improvement, with reduction in purulent discharge and necrotic tissue. Skin integrity improved, and improvements were seen in glycemic control, with a decrease in hypoglycemic and hyperglycemic episodes. Thus, teamwork is essential in the care of patients with diabetic foot and peripheral vascular complications, as well as education, prevention of complications, management of wounds and promotion of a healthy lifestyle are key aspects in the care of these patients to improve their quality of life and prevent serious complications.